2022
DOI: 10.3389/fmicb.2022.903146
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chromate on Pseudomonas aeruginosa Molybdenum Homeostasis

Abstract: Acquisition of the trace-element molybdenum via the high-affinity ATP-binding cassette permease ModABC is essential for Pseudomonas aeruginosa respiration in anaerobic and microaerophilic environments. This study determined the X-ray crystal structures of the molybdenum-recruiting solute-binding protein ModA from P. aeruginosa PAO1 in the metal-free state and bound to the group 6 metal oxyanions molybdate, tungstate, and chromate. Pseudomonas aeruginosa PAO1 ModA has a non-contiguous dual-hinged bilobal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Thus this molybdenate-containing enzyme participates in the anaerobic growth of bacteria ( Van Alst et al, 2009 ). Therefore, the ModA protein plays a pivotal role in nitrate reduction and energy production in bacteria under anaerobic conditions ( Kraft et al, 2011 ; Pederick et al, 2014 ; Maunders et al, 2022 ). Several studies have shown that under anaerobic conditions, the nitrate reduction rate of a modA -mutant strain was reduced and its nitrate reductase activity was also reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Thus this molybdenate-containing enzyme participates in the anaerobic growth of bacteria ( Van Alst et al, 2009 ). Therefore, the ModA protein plays a pivotal role in nitrate reduction and energy production in bacteria under anaerobic conditions ( Kraft et al, 2011 ; Pederick et al, 2014 ; Maunders et al, 2022 ). Several studies have shown that under anaerobic conditions, the nitrate reduction rate of a modA -mutant strain was reduced and its nitrate reductase activity was also reduced.…”
Section: Discussionmentioning
confidence: 99%
“…16 To facilitate molybdenum uptake, P. aeruginosa uses a high-affinity ATP-binding cassette permease, ModABC to recruit and import molybdate from the environment. 16,17 Importantly, the molybdate transporter ModABC was found to be essential for anaerobic growth in an in vivo animal model of chronic lung infection. 18 ModA was shown to be a molybdate-binding protein and important for bacterial competition and virulence of P. aeruginosa in a…”
mentioning
confidence: 99%